Power BI as an auxiliary tool for biostatistics - N. Yu. Dmitrieva (Реальная клиническая практика: данные и доказательства)
Visualization of research results based on data from real clinical practice (RWD) is mandatory when conducting presentations and publishing reports. One of the additional tools that allow you to customize complex reports is the business intelligence service from Microsoft Power BI. The article discusses various ways of loading, processing and visualizing data from clinical registers using the specified software.